1979
DOI: 10.1099/0022-1317-44-2-443
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Wild-type and Cold-mutant (Temperature-sensitive) Influenza Viruses: Independent Segregation of Temperature-sensitivity of Virus Replication from Temperature-sensitivity of Virion Transcriptase Activity during Recombination of Mutant A/Ann Arbor/6/60 with Wild-type H3N2 Strains

Abstract: SUMMARYRNA I* (see end of Summary) of a cold-adapted and temperature-sensitive (ts) influenza virus mutant A/Ann Arbor/6/6o has a different mobility from RNA I of wild-type (wt) A/Ann Arbor/6/6o when subjected to electrophoresis through acrylamide/agarose gels in the absence of denaturing agents. Detection of this lesion in RNA I of the mutant virus was dependent on the temperature of the gel during electrophoresis. Because RNA t is believed to code for a protein involved in virus-specific RNA synthesis we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…However, as it has been demonstrated that RNA segment 1 of fowl plague virus Rostock is functionally equivalent to RNA segment 2 of the WSN strain of influenza virus (Scholtissek, 1978(Scholtissek, , 1979 there is a clear correlation between the results presented here and those obtained in previous studies with influenza WSN (Mowshowitz & Ueda, 1976: Mowshowitz, 1978, influenza A/Ann Arbor/6/60 (Kendal et al, 1978(Kendal et al, , 1979 and fowl plague virus Weybridge (Ghendon et al, 1975). In all cases, a protein encoded in the genome RNA segment functionally equivalent to influenza WSN RNA segment 2 is essential for the function of the virion transcriptase.…”
supporting
confidence: 74%
“…However, as it has been demonstrated that RNA segment 1 of fowl plague virus Rostock is functionally equivalent to RNA segment 2 of the WSN strain of influenza virus (Scholtissek, 1978(Scholtissek, , 1979 there is a clear correlation between the results presented here and those obtained in previous studies with influenza WSN (Mowshowitz & Ueda, 1976: Mowshowitz, 1978, influenza A/Ann Arbor/6/60 (Kendal et al, 1978(Kendal et al, , 1979 and fowl plague virus Weybridge (Ghendon et al, 1975). In all cases, a protein encoded in the genome RNA segment functionally equivalent to influenza WSN RNA segment 2 is essential for the function of the virion transcriptase.…”
supporting
confidence: 74%
“…However, it is also possible that events necessary for mRNAprimed transcription (such as endonuclease activity or associated conformational changes in the polymerase) are not completely decoupled from transcription during ApG-primed synthesis. Consistent with the latter possibility, several ts virus mutants have been found with lesions in the PB2 gene that affect dinucleotide-primed transcription (Kendal et al, 1979;Nichol et al, 1981). Nevertheless, the primary effect of the F5 serum on normally primed synthesis seems to be inhibition of the endonuclease.…”
Section: Discussionsupporting
confidence: 51%
“…At 25 ° C the activities of any influenza wt strains do not surpass their activities at the optimal temperature (11,22). The ca A/AA/6/60 variant and any ca reassortants containing the A/AA/6/60 PB 2 gene, however, exhibited identical activities at both 25 ° and 33 ° C in our assay.…”
Section: Discussionmentioning
confidence: 64%